2014
DOI: 10.1021/jm5006868
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Affinity: Enthalpy–Entropy Factorization Unravels Complexity of a Flat Structure–Activity Relationship for Inhibition of a tRNA-Modifying Enzyme

Abstract: Lead optimization focuses on binding-affinity improvement. If a flat structure-activity relationship is detected, usually optimization strategies are abolished as unattractive. Nonetheless, as affinity is composed of an enthalpic and entropic contribution, factorization of both can unravel the complexity of a flat, on first sight tedious SAR. In such cases, the binding free energy of different ligands can be rather similar, but it can factorize into enthalpy and entropy distinctly. We investigated the thermody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…ITC measurements can record, when studied under different buffer conditions, whether a change in protonation state occurs, and this can drive a tailored design of pK a properties of ligands in order to optimize their binding in parallel with appropriate bioavailability. [30] An ITC experiment observes the total binding event all the way from individually solvated protein and ligand to the formed complex with changed degrees of freedom and it includes all participating water molecules. This will not be disclosed solely by considering affinity data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ITC measurements can record, when studied under different buffer conditions, whether a change in protonation state occurs, and this can drive a tailored design of pK a properties of ligands in order to optimize their binding in parallel with appropriate bioavailability. [30] An ITC experiment observes the total binding event all the way from individually solvated protein and ligand to the formed complex with changed degrees of freedom and it includes all participating water molecules. This will not be disclosed solely by considering affinity data.…”
mentioning
confidence: 99%
“…Finally, ITC data can help to understand flat structureactivity relationships and distinguish ligand binding to alternative conformations of a target protein, an effect that cannot be unraveled solely by considering affinity data. [30] An ITC experiment observes the total binding event all the way from individually solvated protein and ligand to the formed complex with changed degrees of freedom and it includes all participating water molecules. It thus reflects-apart from binding-a more complete picture, including many additional phenomena that give rise to superimposed compensatory effects also resulting from concurrent changes of the protein and solvent environment.…”
mentioning
confidence: 99%
“…The application of thermodynamic data in combination with complex structures in hit-to-lead optimization has been reported in several cases ( Abel et al, 2008 ; Neeb et al, 2014 ; Cramer et al, 2017b ). We also successfully utilized this strategy in the process of lead discovery of phosphodiesterase type 5 (PDE5) and fatty-acid binding protein 4 (FABP4), and found that the water molecule or water network in the ligand binding pocket plays an important role in association of compounds with targeting proteins.…”
Section: Thermodynamic Characterization Of Ligand–target Bindingmentioning
confidence: 99%
“…[c] Values werecalculated with ACD/Percepta [43] at pH 8.0. www.chemmedchem.org off equation on the inhibitory data from the photometric assay. [26,27]…”
Section: Esi-ms Binding Studiesmentioning
confidence: 99%
“…Synthesis and biological activity of designed monosulfonamide ligands 5-(Chlorosulfonyl)isophthalic acid (27)w as converted into compound 28,then monobrominated to provide buildingb lock 29 (Scheme 4). Precursor 30 was prepared followingapublished protocol, [38] reduced to alcohol 31,a nd brominated to afford building block 32.…”
Section: Monosulfonamidei Nhibitors Derived By Rational Designmentioning
confidence: 99%